PROJECT-BASED LEARNING (AN ALTERNATIVE METHOD OF TESOL) - Adriansyah A. Katili (LP2M IAIN Sultan Amai Gorontalo, 2018)
This paper is aimed at proposing the project-based learning as an alternative method of learning. This paper discussed why this method can be considered as an alternative method. Some discussions from some experts are presented.